Directions and Results of Punctuation Management - Drukteinis, Albinas (Lietuvių kalba, 2024)
The article discussed the development of the basics and principles of punctuation in the descriptions of the management of punctuation. The mentioned bases for punctuation—grammar (syntax), meaning, and intonation and pauses—are proposed to be consolidated into two, grammatical (syntactic) and meaning- and intonation-based punctuation, regarding intonation as one of the ways of realizing the meaning of the text. The intonational basis is auxiliary in the realization of the general meaning of the text. It is appropriate to interpret these two bases as criteria for punctuation practice and rule development, and to consider the functionality of the punctuation marks and rules to be the general principle. For specific cases of interpretation of punctuation of syntactic units, the grammatical (syntactic) basis is important. Over the period of 100 years, the regulation of punctuation has largely adhered to a combination of grammatical (syntactic) and meaning- and intonation-based reasoning, only in isolated periods was there a greater tendency toward a more formal syntactic description of punctuation. In the recent period, more and more priority is given to the preferences of the author of the text, if it is necessary for the general meaning of the text. In recent decades, the phenomenon of incomplete, undeveloped or contracted (compressed) structures, which has come increasingly into focus in the descriptions of punctuation, can help to clarify problematic cases of punctuation of altered structures and more accurately define the possibilities of using punctuation marks. Punctuation rules can be made more functional by breaking down syntactic phenomena in more detail and adding previously unexplored syntactic units to the rules.